Nostradamus: Modern Methods of Prediction, Modeling and Analysis of Nonlinear Systems - Zelinka, Ivan.; Rs̲sler, Otto E.; Snàel, Vc̀lav.; Abraham, Ajith.; Corchado, Emilio S. (Advances in Intelligent Systems and Computing, 2013)
This proceeding book of Nostradamus conference (http://nostradamus-conference.org) contains accepted papers presented at this event in 2012. Nostradamus conference was held in the one of the biggest and historic city of Ostrava (the Czech Republic, http://www.ostrava.cz/en), in September 2012. Conference topics are focused on classical as well as modern methods for prediction of dynamical systems with applications in science, engineering and economy. Topics are (but not limited to): prediction by classical and novel methods, predictive control, deterministic chaos and its control, complex systems, modelling and prediction of its dynamics and much more.